1999
DOI: 10.1074/jbc.274.23.16249
|View full text |Cite
|
Sign up to set email alerts
|

Protease Trafficking in Two Primitive Eukaryotes Is Mediated by a Prodomain Protein Motif

Abstract: Trypanosome protozoa, an early lineage of eukaryotic cells, have proteases homologous to mammalian lysosomal cathepsins, but the precursor proteins lack mannose 6-phosphate. Utilizing green fluorescent protein as a reporter, we demonstrate that the carbohydrate-free prodomain of a trypanosome cathepsin L is necessary and sufficient for directing green fluorescent protein to the lysosome/endosome compartment. A proper prodomain/catalytic domain processing site sequence is also required to free the mature protea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 34 publications
(33 reference statements)
2
65
1
Order By: Relevance
“…Therefore a similar analysis of vesicle size was performed in stationary phase promastigotes expressing GFP-ATG8 and proCPB-RFP, which is known to label the lysosome. 4 This more extensive analysis produced similar results, with GFP-ATG8-labeled vesicles exhibiting a mean diameter of 0.36 mm, whereas vesicles labeled with both GFP-ATG8 and proCPB-RFP, or proCPB-RFP alone, had mean diameters of 0.59 mm and 0.53 mm, respectively (Fig. 6B).…”
Section: Characterization Of Autophagosomes and Lysosomes Based On Sisupporting
confidence: 64%
See 2 more Smart Citations
“…Therefore a similar analysis of vesicle size was performed in stationary phase promastigotes expressing GFP-ATG8 and proCPB-RFP, which is known to label the lysosome. 4 This more extensive analysis produced similar results, with GFP-ATG8-labeled vesicles exhibiting a mean diameter of 0.36 mm, whereas vesicles labeled with both GFP-ATG8 and proCPB-RFP, or proCPB-RFP alone, had mean diameters of 0.59 mm and 0.53 mm, respectively (Fig. 6B).…”
Section: Characterization Of Autophagosomes and Lysosomes Based On Sisupporting
confidence: 64%
“…To determine whether this compartment was the lysosome, we employed 2 different markers: FM 4-64 6,21 and proCPB-RFP, the propeptide region of the lysosomal cysteine peptidase B. 4 Both of these markers colocalized with GFP-ATG8 in large structures similar to those colabeled by GFP-ATG8 and RFP-SQL (Fig. 5C), showing that this compartment is the lysosome.…”
Section: Trafficking Of Autophagosomes and Glycosomes To The Lysosomamentioning
confidence: 99%
See 1 more Smart Citation
“…Toxopain-1 does not appear to have mannose 6-P despite two potential glycosylation sites in its prodomain (data not shown). McKerrow and coworkers (40) has identified a prodomain motif in the cathepsin Ls of T. cruzi and Leishmania mexicana, which are required for targeting to lysosomes, but similar signals have not been identified in cathepsin B. We also found that toxopain-1 is released extracellularly into buffer independent of synchronized rhoptry release during invasion.…”
Section: Fig 10supporting
confidence: 54%
“…These positively charged amino acids might be crucial for the structural stability of the prodomain and/or its interactions with proteins required for proper trafficking. Similarly, positively charged residues play a key role in trafficking the cysteine protease cruzain to the lysosome/endosome compartment in the protozoan Trypanosoma cruzi (28). On the cytoplasmic side of the falcipain-2 prodomain, a Phe-Val motif between residues 15 and 25 is conserved across homologues of falcipains (Fig.…”
Section: Discussionmentioning
confidence: 99%